Identifikasi Bahan Tambahan Makanan (BTM) Pada Makanan yang Dijual di Lingkungan UNJANI (Universitas Jenderal Achmad Yani) Cimahi - Lustiana, Tantri; Maharani, Putri; Fatimatul Fauziah, Nur; Denden S, Denny; Nur Aulia, Siska; Juniarty Z, Arni; Ramadhan, Sahrul (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2023)
Because food technology is progressing, there is more and more production, consumption and buying and selling of foodstuffs with more durable packaging. Some foods are sold using food additives. Health can be compromised if food additives are used inappropriately. Data from the cimahi city health office (2011) shows 24% or as many as 41 food samples do not meet health standards (11 samples) contain formalin, (12 samples) contain borax, and (7 samples) contain rhodamine B. This research was conducted to test whether or not there is a presence or absence of rhodamine B in the food. This study was conducted to test the presence or absence of food additives in food in the area around Universitas Jenderal Achmad Yani (UNJANI) as a form of community service so that people are more careful in choosing food. Chromic acid method was used in formalin test, curcumin test in borax test and KLT method in Rhodamine B test. This research was conducted at the Toxicology Laboratory of the Faculty of Technology and Health Sciences, UNJANI. The activities carried out in the study were sampling from peddlers around UNJANI, testing borax, formalin and rhodamine B. In this study, the test results of 5 borax samples, 5 formalin samples and 5 rhodamine B samples were obtained, all of which were negative from harmful Food Additives (BTM). A positive result was obtained on one of the Rhodamine B test samples.